The EFSUMB Guidelines and Recommendations for Musculoskeletal Ultrasound – Part II: Joint Pathologies, Pediatric Applications, and Guided Procedures - Naredo, Esperanza; Rodriguez-Garcia, Sebastián C.; Terslev, Lene; Martinoli, Carlo; Klauser, Andrea; Hartung, Wolfgang; Hammer, Hilde B.; Cantisani, Vito; Zaottini, Federico; Vlad, Violeta; Uson, Jacqueline; Todorov, Plamen; Tesch, Christian; Sudoł-Szopińska, Iwona; Simoni, Paolo; Serban, Oana; Sconfienza, Luca Maria; Sala-Blanch, Xavier; Plagou, Athena; Picasso, Riccardo; Özçakar, Levent; Najm, Aurelie; Möller, Ingrid; Micu, Mihaela; Mendoza-Cembranos, Dolores; Mandl, Peter; Malattia, Clara; Lenghel, Manuela; Kessler, Jens; Iohom, Gabriella; de la Fuente, Javier; DʼAgostino, Maria Antonietta; Collado, Paz; Bueno, Angel; Bong, David; Alfageme, Fernando; Bilous, Diana; Gutiu, Roxana; Marian, Anamaria; Pelea, Michael; Fodor, Daniela (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
The second part of the Guidelines and Recommendations for Musculoskeletal Ultrasound (MSUS), produced under the auspices of EFSUMB, following the same methodology as for Part 1, provides information and recommendations on the use of this imaging modality for joint pathology, pediatric applications, and musculoskeletal ultrasound-guided procedures. Clinical application, practical points, limitations, and artifacts are described and discussed for every joint or procedure. The document is intended to guide clinical users in their daily practice.
Keywords: ultrasound; musculoskeletal; EFSUMB; guidelines; recommendations